Kultura popularna jako przestrzeń edukacyjna – obrazy utopii w tekstach popkultury - Jakubowski , Witold (Studia Edukacyjne, 2018)
The aim of the text is to discuss the educational potential of popular culture. The firstpart focuses on theoretical opinions on the relationships of culture and education. Pedagogical thinking about culture is dominated by its humanistic understanding, in which a special sense of culture has been understood as one of the top of human achievement. In traditional pedagogical reflection,there is noticeable concentration on culture as “valuable for educational interactions”. In such a perspective, the space of popular culture is ignored. Perceived as a bad Mr. Hyde of cultural space, it is treated as an area of threats to the development of children and youth. But culture is not only a canon of the achievements of past generations. In the anthropological sense, these are simply the ways of living a life in a society. Popular culture is the space where various aspects are commented on. Popular art plays a special role here.The second part discusses the pop cultural texts that illustrate the characteristic elements of utopia: burial of the “old world”, establishing a “perfect” order, protection against external destruction and against destruction from inside. Formed at different times and based on different means of expression, they address the dilemmas associated with thinking about a “better world”. They present the mechanisms and consequences of building a new society “with their own language”.